2018
DOI: 10.3389/fphar.2018.00916
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Symptom Relief Following Medical Cannabis Consumption

Abstract: Background: The Releaf AppTM mobile software application (app) data was used to measure self-reported effectiveness and side effects of medical cannabis used under naturalistic conditions.Methods: Between 5/03/2016 and 12/16/2017, 2,830 Releaf AppTM users completed 13,638 individual sessions self-administering medical cannabis and indicated their primary health symptom severity rating on an 11-point (0–10) visual analog scale in real-time prior to and following cannabis consumption, along with experienced side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 39 publications
3
38
0
8
Order By: Relevance
“…Patterns of use are related to subjective effects to cannabis (Daniulaityte et al 2018;Ware et al 2005). Frequency of use, route of administration, and type of cannabinoid used all impact the effects to cannabis (Stith et al 2019;Sexton et al 2016;Stith et al 2018). A comprehensive study of medical cannabis patients found that the primary route of administration was inhalation (84%); oral administration was only 8, and 0.6% used topicals (Peretti-Watel et al 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Patterns of use are related to subjective effects to cannabis (Daniulaityte et al 2018;Ware et al 2005). Frequency of use, route of administration, and type of cannabinoid used all impact the effects to cannabis (Stith et al 2019;Sexton et al 2016;Stith et al 2018). A comprehensive study of medical cannabis patients found that the primary route of administration was inhalation (84%); oral administration was only 8, and 0.6% used topicals (Peretti-Watel et al 2003b).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, based on a review of the literature, participants were allowed to select up to 9 options of reasons for use: relax/unwind, improve mood, help with pain, help with sleep, help with stress, help with depression, glaucoma, nausea/loss of appetite, and neurologic condition. 14 As many participants selected both adult use (eg, relaxation) and medical (eg, glaucoma) reasons, we separately grouped all men who listed a medical reason (ie, medical use) or did not (ie, adult use) in the primary reason for use variable. The complete distribution of the reason for use is illustrated in Supplemental Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Further real-world benefits from CBMPs using patient reports have been reported for Parkinson’s disease ( Balash et al, 2017 ), autism (Bar-Lev Schleider et al, 2019), pain, depression, and anxiety symptoms ( Gulbransen et al, 2020 ). Many patients experience therapeutic satisfaction when using medical cannabis and report improvements in or relief of a range of symptoms ( Gulbransen et al, 2020 ; Stith et al, 2018 ; Sexton et al, 2016 ). Others report using cannabis as an alternative to pharmaceutical prescriptions ( Sith et al, 2018 ) and this can lead to reduced use of opioids for example ( Ueberall et al, 2019 ).…”
Section: Current Evidence Of Medical Valuementioning
confidence: 99%
“…Many patients experience therapeutic satisfaction when using medical cannabis and report improvements in or relief of a range of symptoms ( Gulbransen et al, 2020 ; Stith et al, 2018 ; Sexton et al, 2016 ). Others report using cannabis as an alternative to pharmaceutical prescriptions ( Sith et al, 2018 ) and this can lead to reduced use of opioids for example ( Ueberall et al, 2019 ). Many of these also report that the medical cannabis improves their quality of life ( Bar-Leve Schleider et al, 2019 ; Gulbransen et al, 2020 ; Sith et al, 2018 ).…”
Section: Current Evidence Of Medical Valuementioning
confidence: 99%